2020
DOI: 10.1186/s12916-020-01792-7
|View full text |Cite
|
Sign up to set email alerts
|

LDL-C: lower is better for longer—even at low risk

Abstract: Background Low-density lipoprotein cholesterol (LDL-C) causes atherosclerotic disease, as demonstrated in experimental and epidemiological cohorts, randomised controlled trials, and Mendelian randomisation studies. Main text There is considerable inconsistency between existing guidelines as to how to effectively manage patients at low overall risk of cardiovascular disease (CVD) who have persistently elevated levels of LDL-C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 48 publications
0
59
0
1
Order By: Relevance
“…In the general population, it is dyslipidemia that is the major contributing factor to atherosclerosis, and CVD [ 17 , 18 ]. Our previous studies, among others, have demonstrated that profound lipid abnormalities in renal transplant recipients are present, and not limited solely to increased cholesterol and triglycerides concentrations, but consisting also of severe disturbances of the FA profile [ 6 , 7 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, it is dyslipidemia that is the major contributing factor to atherosclerosis, and CVD [ 17 , 18 ]. Our previous studies, among others, have demonstrated that profound lipid abnormalities in renal transplant recipients are present, and not limited solely to increased cholesterol and triglycerides concentrations, but consisting also of severe disturbances of the FA profile [ 6 , 7 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also important that patients are at LDL-C goal as early as possible and as long as possible, preferably lifelong. Therefore, clinicians should always consider "the lower the better" together with "the earlier the better" and "the longer the better" management strategies [17,18].…”
Section: Ldl-cholesterol Managementmentioning
confidence: 99%
“…Elevated serum low-density lipoprotein cholesterol (LDL-C) is an established risk factor for atherosclerotic cardiovascular (CV) disease [1][2][3]. For the general population and those at increased CV risk, decreasing the LDL-C by dietary adjustment represents the primary method of CV risk reduction and therefore deserves special emphasis in the evaluation of lifestyle changes [2].…”
Section: Introductionmentioning
confidence: 99%